Study on enhancement the antagonistic of Trichoderma koningiopsis against Rhizoctonia solani causing sheath blight in rice by gamma irradiation treatment - Tran, Diep Bang; Tran, Huyen Thanh; Hoang, Dang Sang; Tran, Xuan An; Hoang, Phuong Thao; Nguyen, Xuan Tung; Tran, Hong Nhung; Le, Xuan Vinh (Academia Journal of Biology, 2024)
As targeted mutagenesis techniques become more prevalent for various filamentous fungi, the use of physical mutagen to induce random genetic variations across whole-genome remains an ideal option for genetic improvement. The aim of this study was to investigate the use of gamma radiation to enhance the antagonistic ability of Trichoderma against plant pathogenic fungi. The spore suspensions of Trichoderma koningiopsis VTCC 31435 was irradiated at doses ranging from 0 to 2500 Gy using a gamma Co-60 source at the Hanoi Irradiation Center. The results showed that the number of surviving spores depends on the irradiation dose. Spore numbers decreased sharply in the dose range of 100 to 1200 Gy, at higher doses, the variation in spore numbers was less pronounced. The required radiation dose to kill 90% of the total number of fungal spores (D10) of the T. koningiopsis VTCC 31435 strain was approximately 250 Gy. At a dose of 2500 Gy, the number of fungal but surviving spores decreased by about 7 Log units compared to the non-irradiated. After irradiation, morphological changes, as well as growth characteristics, were observed in some of the radiation-resistant obtained colonies. Using cellophane membrane assay and dual culture methods, five potential radiation-resistant mutants with better antagonistic ability against the fungus Rhizoctonia solani, which causes sheath blight in rice, were identified Notably, among these, the potential mutant VTCC(a) I-1 exhibited the highest antifungal activity of media-permeable metabolites (ICMA) and mycelial growth inhibition activity (IMG) against R. solani. The ICMA and IMG values of this mutant increased by 154.12% and 148.68%, respectively, compared to the wild-type strain and remained stable for at least six consecutive generations. The research results suggest that gamma irradiation may have potential applications in enhancing the antagonistic abilities against pathogenic fungi and other beneficial biological properties in Trichoderma sp.